Effect of acupressure on nausea and vomiting during pregnancy - CAN GÜRKAN, ÖZLEM (My University, 2008)
This paper sought to determine the efficacy of acupressure application in pregnant women suffering from nausea, with or without associated vomiting, who were unable to receive conventional medication for these symptoms. Sampling consisted of pregnant women complaining of nausea with or without vomiting. The study was controlled by the Maternity and Child Hospital in Istanbul between March 2004 and March 2005. The treatment group comprised 26 women; 25 in the control arm and 24 women were assigned to the placebo arm. The study occurred over a 9-day period. During this time, the treatment group applied acupressure bands to P6 acupressure point on days 4-6 of the study with the placebo group receiving acupressure bands to a sham acupressure point, on the upper side of their wrists. Results and conclusion: Acupressure would appear to be effective in symptom control, and alleviation and placebo effects in reducing the symptoms of nausea and vomiting during pregnancy. © 2007 Elsevier Ltd. All rights reserved.
Keywords: Acupressure; Nausea; Vomiting of pregnancy